Evaluation of the Structural Behavior of Prestressed Concrete Bridge Girders under Diagnostic Load: A Test-Case Study - Abdulrazzaq, Oday A.; Kadim, Jaffar A.; Mohammed , David Abed (Engineering, Technology & Applied Science Research, 2025)
This study deals with the structural behavior of prestressed concrete bridge girders consisting of 4 spans using the field diagnostic load test method and comparing the results with the mathematical model of the CSiBridge program. The bridge under study is located in the city of Basra in southern Iraq and was constructed more than 40 years ago, which makes it necessary to determine the actual structural conditions in order to decide whether it is safe to keep using it or not. A 48.5 tn vehicle was used for the test, where each area was divided into 3 load paths, and then the site data values were simulated utilizing the CSiBridge program. The field test data cleared the durability of the bridge for all spaces from any structural defects, and the correlation test results were very close with the analytical study results. The field results indicate that half of the lanes tested behave linearly and the other half behave non-linearly, with the source of the non-linearity being related to the potential problems of the prestressed girders. The theoretical results also proved that vehicles with a load of 72.4 tn can go through, without causing any damage to the different parts of the bridge.